2019
DOI: 10.1016/j.metabol.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia drives hepatic insulin resistance in male mice with liver-specific Ceacam1 deletion independently of lipolysis

Abstract: Background: CEACAM1 regulates insulin sensitivity by promoting insulin clearance. Accordingly, global C57BL/6J.Cc1 −/− null mice display hyperinsulinemia due to impaired insulin clearance at 2 months of age, followed by insulin resistance, steatohepatitis, visceral obesity and leptin resistance at 6 months. The study aimed at investigating the primary role of hepatic CEACAM1 in insulin and lipid homeostasis independently of its metabolic effect in extra-hepatic tissues. Methods: Liver-specific C57BL/6J.AlbCre+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 51 publications
(89 reference statements)
6
41
0
Order By: Relevance
“…Previous articles reported that the hepatic CEACAM1 expression was markedly decreased in the severely obese subjects, high grade fatty livers and NASH, but not different between diabetic and non-diabetic persons [20]. Consistent with this study, some researchers also indicated that CEACAM1 mRNA levels were declined significantly in the liver of obese humans and obese rats, as expected, the obese rats then displayed hyperinsulinemia, elevated body weight, fasting plasma free fatty acid, and plasma and hepatic total triglycerides levels [21,22]. These studies suggested that the decreased CEACAM1 levels might be an early event in obese subjects occurring at the time of insulin resistance before overt diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Previous articles reported that the hepatic CEACAM1 expression was markedly decreased in the severely obese subjects, high grade fatty livers and NASH, but not different between diabetic and non-diabetic persons [20]. Consistent with this study, some researchers also indicated that CEACAM1 mRNA levels were declined significantly in the liver of obese humans and obese rats, as expected, the obese rats then displayed hyperinsulinemia, elevated body weight, fasting plasma free fatty acid, and plasma and hepatic total triglycerides levels [21,22]. These studies suggested that the decreased CEACAM1 levels might be an early event in obese subjects occurring at the time of insulin resistance before overt diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Fed a regular chow diet, mice with global Ceacam1 deletion (Cc1 −/− ) and liver-specific deletion (AlbCre + Cc1 fl/fl ) and inactivation (L-SACC1) manifested hyperinsulinemia-driven insulin resistance, early stage NASH (steatohepatitis with hepatic fibrosis), and visceral obesity. (17,35,36) In addition to this cluster of metabolic abnormalities, Cc1 −/− mice developed several cardiovascular features of metabolic syndrome: endothelial dysfunction, hypertension, kidney dysfunction, cardiac dysfunction with myocardial hypertrophy, and small intimal plaque-like lesions with fat and macrophage deposition in aortae. The restricted size of these aortic lesions (~5-fold smaller than ApoE −/− ) (21) was attributed to their limited lipidemia (elevated plasma NEFA in the absence of hypercholesterolemia or hypertriglycedemia).…”
Section: Discussionmentioning
confidence: 99%
“…geneRation oF liVeR-speCiFiC AlbCre + Cc1 fl/fl null miCe pRopagateD on an Ldlr −/− BaCKgRounD C57BL/6J.AlbCre + Cc1 fl/fl mice were generated, as described, (17) and backcrossed >6 times with Ldlr −/− ;B6.129S7-Ldlrtm1Her/J ( JAX#002207; Jackson Laboratory, Bar Harbor, ME). Offspring were genotyped by polymerase chain reaction (PCR) analysis of ear DNA, using Ceacam1-specific primers (Supporting Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Since CEACAM2 is not expressed in skeletal muscle [8], the progressive age-related decline in energy dissipation in Cc2 −/− males likely stems from central dysregulation of peripheral glucose disposal, as is the case for their female counterparts [15]. Given that hypothalamic Ceacam2 mRNA level remains intact with age, unlike that of Ceacam1 that declines progressively until it reaches a loss by >70% at nine months of age to contribute to hyperphagia and disturb energy balance [58], it is likely that reduced Ceacam1 mRNA amplifies the adverse effect of Ceacam2 deletion on the hypothalamic control of glucose disposal and energy expenditure in older Cc2 −/− males.…”
Section: Role Of Ceacam2 In Food Intake: Effect On Insulin Actionmentioning
confidence: 99%
“…In males, the persistent increase in insulin secretion, in part mediated by the higher plasma GLP-1 secretion [13], is offset by a parallel increase in CEACAM1-mediated insulin clearance, resulting in normoinsulinemia in the young until ~9 months of age when chronic hyperinsulinemia develops largely from impaired hepatic insulin clearance that fails to counter the sustained elevation in insulin secretion [14]. Impaired insulin extraction in older males, results from the age-related progressive decline in hepatic CEACAM1 levels [14,58]. Nonetheless, hyperinsulinemia induces the transcriptional activity of SREBP-1c to stimulate the expression of lipogenic genes [70], such as fatty acid synthase (FASN), followed by their activation.…”
Section: Role Of Ceacam2 In Food Intake: Effect On Insulin Actionmentioning
confidence: 99%